Negarbingi kiti - Horntvedt, Tone (Information & Media, 2008)
Šiame pranešime autorius aptaria, kaip diskurso sistemos gali kurti ir deformuoti sąveiką tarp profesionalų ir jų klientų. Diskusija grindžiama epizodu, veiksmo vieta – parkas Norvegijoje 2007 metų vasarą, ir tuo metu aptariamos tokios temos:1. Apibrėžimų galia diskursuose. Ar galima teigti, kad apibrėžimai gali dominuoti ir kad jais Santraukaremiantis yra projektuojamas ir keičiamas realybės suvokimas?2. Poreikis projektuoti etnocentriškumo sindromą;3. Poreikis įtraukti į diskusiją tiek mūsų suvokimą, tiek marginalijų derinių realybę.The unworthy othersTone HorntvedtSummaryThis paper is based on an incident which took place this August in a park in Oslo.The incident was as follows; a severely beaten Somali man was left by the Emergency Medical Technicians (EMTs), because they thought he was a drug addict. What made this incident different from other episodes was that it took place on a summer afternoon and he was surrounded by his wife, friends and health care workers who all told the EMTs that he was not a drug addict. In this paper I will discus whether what happened here was one version of meetings between representatives of the Norwegian welfare system and its users they see as marginalized. I will look into: 1. The power of definitions in discourses. Is it possible that these definitions can be so dominant that they project and twist the perception of reality? 2. The possible need to project, embodied in the Ethnocentric Syndrome; 3. Can we put under discussion both our perceptions and the reality of marginalized groups?Key words: perception, marginalization, ethnocentric syndrome, professional discourses